Mari Mengeja: Edisi Jawi - Zainon, Nur Fatin Izzatie; Saman, Fadhlina Izzah; Ahmad Affendy, Ahmad Haziq Aiman (2020)
Nowadays, current education system does include Jawi such as inj-QAF programmed and Pendidikan Islam subject in school. However, from the researches and survey conducted, it is found that Jawi education in Malaysia is still taught using traditional ways such as using flash card and textbook, that has less interactivity which causes student to have difficulty in maintaining their concentration. Learning Jawi in class is bound to limited time and learning Jawi words is cognitively complex due to the number of rules applied. The purpose of this project is to give an alternative learning material to those who are interested in learning Jawi by using game-based learning approach which implements game elements such as repetition, reward system and penalty in the gameplay. This project is built in mobile device which let people learn ubiquitously.This project uses Game Development Life Cycle (GDLC) model approach where it has six phases which are initiation, pre-production, production, testing, beta and release phase. Game Based Learning (GBL) model is used as the guide in developing the game concept to ensure that the game is developed in line with the learning Jawi intention despite it being a game. At the end of the project, the Game Based Learning application has been successfully developed. However, some future works have also been identified to further improve the game such as to add various avatars, adding multi-language function and making it available for multiplatform.